2015
DOI: 10.2106/jbjs.n.00948
|View full text |Cite
|
Sign up to set email alerts
|

Hemicortical Resection and Inlay Allograft Reconstruction for Primary Bone Tumors

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 43 publications
2
18
1
Order By: Relevance
“…2), which have presumably higher consolidation rates due to the larger contact area as well as the lower extent of soft tissue dissection [7]. Similar to our results, comparable studies on hemicortical reconstructions with auto- or allografts following tumour resection showed lower non-union rates of only 0–7% [7, 3336]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…2), which have presumably higher consolidation rates due to the larger contact area as well as the lower extent of soft tissue dissection [7]. Similar to our results, comparable studies on hemicortical reconstructions with auto- or allografts following tumour resection showed lower non-union rates of only 0–7% [7, 3336]. …”
Section: Discussionsupporting
confidence: 87%
“…This is in accordance with reports in the literature, where the superiority of vascularised fibulae over non-vascularised grafts was reported for bone defects longer than 12 cm as indicated by failure rates of 25% and 50%, respectively, [38]. The significantly lower mechanical complication rate of hemicortical reconstructions ( p  = 0.013) in our series might be explained—beside the above mentioned factors such as the limited extent of soft-tissue dissection and a greater contact surface between graft and host bone—by the preservation of cortical continuity [7]. Taking our own results into account, we therefore strongly recommend the use of vascularised fibula grafts for segmental bone defects of 12 cm or greater.…”
Section: Discussionmentioning
confidence: 59%
“…The most frequent complication in this study was host bone fracture, with a reported rate of 15% to 27% in previous studies that evaluated more than 10 patients (8-10, 13). First, perfect fitting of the allograft may reduce fracture rate (8,15). Contrary to the allograft, it is relatively easy to obtain perfect cortical apposition between the irradiated autologous bone and host cortices at the junction.…”
Section: Discussionmentioning
confidence: 99%
“…However, non-union in intercalary reconstructions using extracorporeal irradiated autologous bone grafts with vascularized fibular grafts has been reported to occur in 7-31% of all patients (5)(6)(7). In contrast, hemicortical resection and reconstruction using allograft or autograft for selected bone and soft tissue malignant tumors yield excellent oncologic and functional outcomes (8)(9)(10)(11). Hemicortical resection may be also indicated for a soft tissue sarcoma (STS) attached to the surface of the bone.…”
mentioning
confidence: 99%
“…Segmental resection in a young child is associated with a high complication rate like fractures in hemicortical resection in 6 of 22 patients [1]. Ingrowth of the reconstruction allograft can be better if CAS is used for a better fit [2], however in general the reconstruction with allograft has high complication rates of up to 40% pseudarthrosis, infection and fracture [3]. To avoid these complications it would be ideal to spare the continuity of tibial bone by treating the tumor in situ.…”
Section: Introductionmentioning
confidence: 99%